2016
DOI: 10.3906/tar-1409-117
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of variation for within-boll yield components in cotton

Abstract: Cotton productivity on a per-hectare basis is low in Pakistan. As boll is the basis for seed cotton yield, within-boll yield components can potentially serve as the most basic determinants of cotton productivity on a per unit land area basis. Before attempting the improvement of any trait, it is necessary to know the genetic mechanism lying behind its inheritance. The current study aimed to estimate the genetic basis of within-boll yield components in cotton. The research trials were conducted at the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
(19 reference statements)
4
9
0
Order By: Relevance
“…These results are in accordance with Basal and Turgut (2005); Basal (2009); Imran et al (2012) and Tang and Xiao (2013). Subhan et al (2003); Pushpam and Raveendran (2005); Ali et al (2011);Ali et al (2015) indicated the preponderance of non-additive genetic effects for seed cotton yield attributes and fibre quality traits. Yuan et al (2001) and Ashraf and Ahmad (2000) advocated additive gene action owing to higher GCA variances.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results are in accordance with Basal and Turgut (2005); Basal (2009); Imran et al (2012) and Tang and Xiao (2013). Subhan et al (2003); Pushpam and Raveendran (2005); Ali et al (2011);Ali et al (2015) indicated the preponderance of non-additive genetic effects for seed cotton yield attributes and fibre quality traits. Yuan et al (2001) and Ashraf and Ahmad (2000) advocated additive gene action owing to higher GCA variances.…”
Section: Discussionsupporting
confidence: 84%
“…Lint mass per boll and number of seeds per boll displayed 36.4 to 48.4% increase over parents and exhibited dominance genetic effects. Ali et al (2015) indicated preponderant effect of dominance variance in the expression of within-yield traits. They also reported involvement of inter-genic interactions in the phenotypic outcome of the traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A production of about 13 million bales was obtained from 2.88-million hectares during the year 2012-13 (Anonymous, 2012-13) which was 4.2 % less than produced in 2011-12. Cotton productivity on unit land area basis, in Pakistan, is low as compared to many leading cotton producing countries of the world (Ali et al, 2015). Not only is the yield, fiber quality is also low in most of the locally developed upland cotton cultivars when compared with rest of the world cotton producers.…”
Section: Introductionmentioning
confidence: 98%
“…Seeds per boll, boll number per unit area and lint mass per seed are the important factors in enhancing cotton yield (Worley et al, 1974). Lint production can be increased by increasing the number of productive seeds, producing more lint fibers, hence increasing the surface area for increased lint production (Ali et al, 2015). Predominance of non-additive genes for bolls per plant, boll weight and seed cotton yield was reported by Waldia et al (1980) and Ahuja and Dhayal (2007), while Kumaresan et al (1999) documented the predominance of both additive and dominance gene action for seed cotton yield and boll number.…”
Section: Introductionmentioning
confidence: 99%